2016
DOI: 10.1007/s10616-016-9974-1
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress increases cytotoxicity and reduces transfection efficiency of liposomal gene delivery to CHO-S cells

Abstract: Animal cells in suspension experience shear stress in different situations such as in vivo due to hemodynamics, or in vitro due to agitation in large-scale bioreactors. Shear stress is known to affect cell physiology, including binding and uptake of extracellular cargo. In adherent cells the effects of exposure to shear stress on particle binding kinetics and uptake have been studied. There are however no reports on the effect of shear stress on extracellular cargo delivery to suspension cells. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…According to simulations, the peak wall shear stress was 20.2 dynes cm −2 (Tesla‐like mixer) and 19.7 dynes cm −2 (HC mixer), respectively. Rawat and Gadgil reported that shear stresses of up to 220 dynes cm −2 lead to slightly lower cell growth, while 2000 dynes cm −2 lead to severe cell damage . Additionally, even shear stress of 2 dynes cm −2 lowered the transfection efficiency, thus shear stress should be kept at an absolute minimum to ensure reliable and efficient transfection in the target application.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to simulations, the peak wall shear stress was 20.2 dynes cm −2 (Tesla‐like mixer) and 19.7 dynes cm −2 (HC mixer), respectively. Rawat and Gadgil reported that shear stresses of up to 220 dynes cm −2 lead to slightly lower cell growth, while 2000 dynes cm −2 lead to severe cell damage . Additionally, even shear stress of 2 dynes cm −2 lowered the transfection efficiency, thus shear stress should be kept at an absolute minimum to ensure reliable and efficient transfection in the target application.…”
Section: Resultsmentioning
confidence: 99%
“…Rawat and Gadgil reported that shear stresses of up to 220 dynes cm −2 lead to slightly lower cell growth, while 2000 dynes cm −2 lead to severe cell damage . Additionally, even shear stress of 2 dynes cm −2 lowered the transfection efficiency, thus shear stress should be kept at an absolute minimum to ensure reliable and efficient transfection in the target application. Therefore, the HC mixer design is most suitable for efficient mixing of CHO‐K1 cells and other biological applications, which require rapid sample mixing at low shear stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear stress was calculated using the equations from the manufacturer’s technical specifications τ=η×104.7×Φ or τ=η×906.0×Φ for 400 and 100 μm tall channels respectively where τ,η,Φ are shear stress (dyne/cm 2 ), dynamic viscosity (dyn.s/cm 2 ) and flowrate (mL/min) respectively. In the literature, the effect of shear stress on nanoparticle uptake ( Jurney et al, 2017 ), cytotoxicity ( Rawat and Gadgil, 2016 ) and molecular delivery ( Meacham et al, 2018 ) is very well established. However, the amount of shear stress in such investigations is typically on the order of 10–100 dyne/cm 2 , which is many orders of magnitude higher than the shear stress in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Turning or rotary paddles, which enable quick exchange of dissolved air, is also a common suspension culture system. Faster stirring improves the efficiency of mixing, although the shear stress increases, resulting in cell damage (Rawat, 2016). However, if stirring is slowed down, the efficiency of mixing decreases, and uniformity of the culture medium may be lost.…”
Section: Introductionmentioning
confidence: 99%